Post-Pandemic Informal Employment of Handicrafts Firms in Kathmandu Valley - Adhikari, Padma Kumar (Humanities and Social Sciences Journal, 2023)
This study tries to examine the informal economic activities during the post-pandemic period on the basis of primary data analysis. The data were generated during the pre-pandemic period whereas the main attributes of economic activities have been compared to the post-pandemic periods. The labours of informal employment in handicrafts firms in the pre-pandemic period have completed just 6.19 classes of education—unorganized and untrained—termed as unskilled with low production efficiency. Their income was estimated with an average of Rs. 23417.84 per month just to survive workers for family level in the capital city of Kathmandu.The family’s monthly income was highly impacted (1640.965 at p < 1%) by the allocation of average per day working hours (12.66 hrs.) on a family basis. In the lockdown situation, informal workers were unemployed completely—reached poor conditions—returned to their homes all 54 percent of migrated and homeless workers in Kathmandu Valley. However, during the post-pandemic situation, all informal workers in the Valley shifted their occupation from handicrafts to other side wage earners shocked by the lockdown. Informal economic activities in this sector are still facing different challenges of social security, job guarantees, and social networking facilities provided by the government. Their estimated monthly income does not seem to be sufficient due to the present increasing inflationary rate of 8.5 percent. Thus, growing informal economic activities are the cause of the hard lockdown during the pandemic of COVID-19. Similarly, the Ukraine-Russia war and undecided government policies have made the situation further worse.